Analisis Implementasi Higiene dan Sanitasi dalam Program Makan Bergizi Gratis Berdasarkan Peraturan Menteri Kesehatan Nomor 2 Tahun 2023 Perspektif Siyasah Tanfidziyyah - Ardiyan Syah Abdi Negara (Jurnal Hukum Lex Generalis, 2025)
This study aims to analyze the implementation of hygiene and sanitation in the Free Nutritious Meal Program based on the Minister of Health Regulation Number 2 of 2023, as well as to examine its conformity with the perspective of Islamic law, particularly the concept of Siyasah Tanfidziyyah. This research is an empirical study employing a qualitative approach, conducted through field research methods, including interviews, observations and documentation, involving the management of the Nutritional Fulfillment Service Unit (SPPG) Sukarame 1 and the Bandar Lampung City Health Office. The findings indicate that the implementation of hygiene and sanitation has generally been carried out; however, several issues remain, such as the inconsistent use of personal protective equipment, limited supervision of hygiene standards and waste management practices that have not fully complied with applicable regulations. From the perspective of Islamic law, these conditions suggest that the principles of al-tanfidz, hifz al-nafs and maslahah have not been optimally realized in practice. Therefore, operational measures are required, including strengthening supervision and periodic evaluation, providing technical training on hygiene and sanitation for program managers and enhancing coordination between SPPG and the Health Office to ensure that policy implementation runs optimally and in accordance with the principles of Islamic law.